Culture and communication: music, song and dance as medium of communication in Africa - Darkwa, Asante (África, 1987)
Traditional music, song, and dance were in the past closely integrated with social life – with the pattern of social organization, with religions behaviour, economic activities and with political organization. Music and dance were very functional in the sense that they accompanied many activities of the daily life of the people. Although the recent forces of acculturation have had some impact on the traditional music, song, and dance practices in many parts of Africa, many of the performing arts traditions which have continued to be closely identified with traditional institutions, ceremonies, rituals and others, have survived the impact and still exist, mostly in the rural areas. The many raiding and war songs of the people which are not heard these days because of social changes, have now become a feature of political rallies. These songs are sung by contemporary dance groups which  praise politicians and other important personalities in song and dance.